Philosophy of Scientific Theories as a Branch of Theoretical Philosophy. Part I - Kuznetsov, Volodymyr; Oriekhova, Arina; Sahan, Maksym (Sententiae, 2025)
Interview by Arina Oriekhova and Maksym Sahan with Volodymyr Kuznetsov, dedicated to the state of the Ukrainian philosophy of science in the 1960s–1980s.